Формування інформаційної культури користувачів бібліотек ВНЗ - Головач, Валентина; Кудлай, В’ячеслав (Видавництво Львівської політехніки, 2017)
In this paper the university library’s impact on student’s informational culture development is observed. The relevant methods and forms used extensively by university libraries to increase user’s information culture are outlined. New forms of services that are implemented using multimedia products and information technology are analysed.
Keywords: бібліотечно-інформаційне обслуговування; інформаційна культура; інформаційна грамотність; процес навчання; суспільство